(untitled) (Journal of actual problems of jurisprudence, 2019)
In article the general concepts of safety in the form of the provision of the public relations, importance of economic, political, military, scientific and technical, social, environmental and other problems of safety as a type of formation of exact concept of safety of these relations in all spheres are considered. Key words: The prison security, criminalized enforcement law, educational and correctional work, labor, convicted, custody.